2002
DOI: 10.1111/j.0014-3820.2002.tb00850.x
|View full text |Cite
|
Sign up to set email alerts
|

Population and Colony Genetic Structure of the Primitive Termite Mastotermes Darwiniensis

Abstract: The termite Mastotermes darwiniensis is the sole extant member of its family and occupies the basal position in the phylogeny of the eusocial order Isoptera. In this study, we investigated the micro- and macrogeographic genetic structure of M. darwiniensis in its native range in Australia. A total of 1591 workers were sampled from 136 infested trees in 24 locales. Each locale was separated by 2-350 km, and these locales were found within two broader geographic regions approximately 1500 km apart. The multilocu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
64
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 45 publications
4
64
0
2
Order By: Relevance
“…This was expected from their life history (Roisin, 1993;Thorne et al, 1999), has already been shown across regional scales in this species (Clément, 1981), and has been described in several other termite species (Thompson and Hebert, 1998;Bulmer et al, 2001;Goodisman and Crozier, 2002;Vargo, 2003a;DeHeer and Vargo, 2004). The underlying causes of this variation remain unclear.…”
Section: Cj Deheer Et Almentioning
confidence: 53%
See 1 more Smart Citation
“…This was expected from their life history (Roisin, 1993;Thorne et al, 1999), has already been shown across regional scales in this species (Clément, 1981), and has been described in several other termite species (Thompson and Hebert, 1998;Bulmer et al, 2001;Goodisman and Crozier, 2002;Vargo, 2003a;DeHeer and Vargo, 2004). The underlying causes of this variation remain unclear.…”
Section: Cj Deheer Et Almentioning
confidence: 53%
“…In contrast to the Hymenoptera where supernumerary queens tend to outbreed (Keller, 1995;Ross, 2001), termite colonies headed by multiple same-sex reproductives usually exhibit equal or higher nestmate relatedness to colonies with a single pair of breeders, presumably because new reproductives of both sexes are typically recruited from the offspring of the original king and queen (Reilly, 1987;Luykx, 1993;Bulmer and Traniello, 2002b). However, there are sporadic reports of termite colonies with unexpectedly low nestmate relatedness (Clément, 1981;Jenkins et al, 1999;Goodisman and Crozier, 2002;Bulmer and Traniello, 2002b;DeHeer and Vargo, 2004;Dronnet et al, 2005), and several authors suggested that these have resulted from a breakdown in nestmate recognition. Although relatedness within these colonies is generally still much higher than zero, they still provide an interesting parallel to the existence of highly polygynous 'supercolonies' seen in some ant species, which in some cases have been shown to result from a collapse in recognition ability (Morel et al, 1990;Holway et al, 1998;Giraud et al, 2002;Tsutsui et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Korb and Schneider (2007) also reported a record of mixed colonies representing 25% of those sampled. Mixed family colonies have been recorded in a number of termite species, including R. flavipes Vargo 2004, DeHeer andKamble 2008), R. grassei Clement (Clement 1981, Clement et al 2001, Mastotermes darwiniensis Froggatt (Goodisman and Crozier 2002), Macrotermes michaelseni Sjostedt (Hacker et al 2005), and Zootermopsis nevadensis Hagen (Aldrich and Kambhampati 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge of the genealogical relationships makes possible many studies in behavioral, ecological, and evolutionary genetics and in conservation biology. Pedigree information is valuable, for example, in studies of social behavior or organization (e.g., Hamilton 1964;Morin et al 1994), mating systems (e.g., Heg and van Treuren 1998;Engh et al 2002), dispersal (e.g., Devlin and Ellstrand 1990;Streiff et al 1999;Chapman et al 2003), and isolation by distance and spatial genetic structure (e.g., Goodisman and Crozier 2002) in natural populations. It also finds applications in locating genes influencing quantitative traits (Spielman et al 1993;Allison et al 1999), estimating the total number of breeders in a population (e.g., Nielsen et al 2001;Pearse et al 2001), inferring the variance of reproductive success among individuals and thus the strength of sexual selection (e.g., Aldrich and Hamrick 1998;Morgan and Conner 2001), estimating quantitative genetic parameters such as heritability (e.g., Ritland 2000; Garant and Kruuk 2005;Thomas 2005), and managing the conservation of populations of endangered species (e.g., Painter 1997;Jones et al 2002).…”
mentioning
confidence: 99%